SPIRITUALITY IS THE BASIS OF HUMAN MATURITY AND THE DEVELOPMENT OF SOCIETY - Aminova Manzura Mutalibovna; Xabibullaeva Muxlisa (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article highlights the role and significance of spirituality in the maturation of a person. The authors pay attention to spirituality in the new period of development of Uzbekistan, in the decrees and decrees of the President of Uzbekistan, information is given about the improvement of spirituality and its causes. Spirituality, according to the conclusion of the authors of the article, is one of the main criteria for the development of man and society.